The Assessment of 3D Digital Models Using GOSLON Yardstick Index: Exploring Confounding Factors Responsible for Unfavourable Treatment Outcome in Multi-Population Children With UCLP - Haque, Sanjida; Khamis, Mohd Fadhli; Alam, Mohammad Khursheed; Wan Ahmad, Amir Wan Muhamad (Frontiers in Pediatrics, 2021)
To evaluate dental arch relationship (DAR) using GOSLON Yardstick and also to explore the association between multiple factors (age, gender, UCLP types, UCLP side, Family history of cleft, family history of Class III malocclusion, techniques of cheiloplasty, techniques of palatoplasty) and DAR in children unilateral cleft lip and palate (UCLP) in different populations. 255 laser scanned 3D digital models (LS3DM) of UCLP children (5-12 years) from Malaysia, Bangladesh, and Pakistan were included. The intra- and inter-examiner agreements were evaluated by kappa statistics, to compare the GOSLON mean score between the populations and to explore the responsible factors that affect DAR, one way ANOVA, and crude logistic regression analysis was used respectively. The mean GOSLON score was 2.97; 3.40 and 3.09 in Malaysia, Bangladesh, and Pakistan respectively. 27, 40 and 30 subjects were in unfavourable (category rating 4 and 5) groups in Malaysia, Bangladesh, and Pakistan respectively. A significant association was found between techniques of palatoplasty (p = 0.03; p = 0.04 and p = 0.04 in Malaysia, Bangladesh, and Pakistan respectively) and unfavourable DAR. Different cheiloplasty techniques (p = 0.04) and gender (p = 0.03) also exhibited noteworthy associations with unfavourable DAR in the Bangladeshi population. Bardach techniques of palatoplasty were significantly associated with unfavourable DAR in all three populations. Moreover, male UCLP and modified Millard techniques of cheiloplasty were also associated with unfavourable DAR in the Bangladeshi population.